Case reportProximal ductus arteriosus stenosis after the hybrid stage I procedure in a newborn with hypoplastic left heart syndrome - Chojnicki, Maciej; Haponiuk, Ireneusz; Steffens, Mariusz; Jaworski, Radoslaw; Szofer-Sendrowska, Aneta; Juscinski, Jacek; Kwasniak, Ewelina (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We present a case of a severely ill newborn with hypoplastic left heart syndrome after the hybrid stage I procedure, with right systemic ventricle insufficiency due to proximal ductus arteriosus stenosis. The child was successfully treated with percutaneous second PDA stent implantation.